2011
DOI: 10.1108/17473611111114795
|View full text |Cite
|
Sign up to set email alerts
|

Tween girls' perception of gender roles and gender identities: a qualitative study

Abstract: Purpose -The present study aims to examine girls' perception of gender roles and gender identities in Hong Kong.Design/methodology/approach -A total of 16 girls aged 10 to 12 were asked to take pictures from the media that could illustrate ''what girls or women should or should not be; and what girls or women should or should not do''. Qualitative interviews were conducted.Findings -Analysis of interviews and images captured found that tween girls' perceived gender roles for females were based on a mixture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…It is the internalized societal pressure of gender conformity that causes an adolescent to form his or her beliefs or behaviors to fit in with or be accepted by religion, society, or culture (Bem, 1981). For example, pre-adolescent girls reported that girls should not behave like boys (Chan et al, 2011). They categorized themselves as the girl group and rejected having characteristics of the boy group.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…It is the internalized societal pressure of gender conformity that causes an adolescent to form his or her beliefs or behaviors to fit in with or be accepted by religion, society, or culture (Bem, 1981). For example, pre-adolescent girls reported that girls should not behave like boys (Chan et al, 2011). They categorized themselves as the girl group and rejected having characteristics of the boy group.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It interacts with attributes of self-perception and gender stereotypes on gender identity (e.g., I am gentle and girls are gentle, so I am a girl). When girls who perceive themselves as brave were asked to select images in the media, they preferred media celebrities who dare to express themselves (Chan et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The statements were derived from those used in a qualitative study of perceptions of gender roles among girls aged 15 to 18 in Hong Kong [31]. Sample statements included -Females should appreciate their own strengths‖, -Females who bear children enjoy a complete life‖ and -Females should not pursue a slim body at all cost‖.…”
Section: B Independent Variablesmentioning
confidence: 99%